P22-17 Cell mechanisms induced by doxorubicin-loaded UCNP@MSN nanoparticles with a thermos-responsive nanovalve in melanoma cells - P. Oskoei; L.-M. Keller; E. Anderson; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2025)

P01-46 Effects of doxorubicin-loaded UCNP@MSN core-shell particles with a thermoresponsive nanovalve in melanoma cells - P. Oskoei; J. Nogueira; L.-M. Keller; E. Andresen; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2024)

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

Perivascular cells of the supraspinatus tendon express both tendon- and stem cell-related markers - Herbert Tempfer; A. Wagner; R. Gehwolf; C. Lehner; M. Tauber; H. Resch; H. C Bauer (Histochemistry and Cell Biology, 2009)

Different Curcuminoids Inhibit T-Lymphocyte Proliferation Independently of Their Radical Scavenging Activities - Michael Deters; Heiko Knochenwefel; Daniel Lindhorst; Therese Koal; Hartmut H. Meyer; Wolfram Hänsel; Klaus Resch; Volkhard Kaever (Pharmaceutical Research, 2008)

Large-scale lateral spreading and related mass movements in the Northern Calcareous Alps - J. Rohn; M. Resch; H. Schneider; T. M. Fernandez-Steeger; K. Czurda (Bulletin of Engineering Geology and the Environment, 2004)

Rasche Carboxihmoglobinbestimmung mittels nichtdispersiver Ultrarot-Gasanalyse - H. Hauck; M. Neuberger; W. Resch (Archives of Toxicology, 1976)